2018
DOI: 10.1002/ejoc.201701775
|View full text |Cite
|
Sign up to set email alerts
|

Selenomethoxylation of Alkenes Promoted by Oxone®

Abstract: We describe herein an alternative method for the selenomethoxylation of unactivated alkenes using Oxone® as a stoichiometric oxidant. The electrophilic species of selenium were easily generated in situ by the reaction of diorganyl diselenides with Oxone®. By this efficient and simple approach, β‐methoxy‐selenides were obtained in moderate to excellent yields at room temperature in an open flask, starting from alkenes by using methanol as both nucleophile and solvent. When a mixture of H2O/CH3CN was employed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 50 publications
3
22
0
1
Order By: Relevance
“…Based on our results and those from the literature (Zhang, Sarkar & Larock, 2006;Recchi, Back & Zeni, 2017;Perin et al, 2018), a plausible mechanism for the carbocyclization of alkynol 1a with (C 6 H 5 Se) 2 2a/Oxone ® in aqueous medium is depicted in Scheme 2. The first step in the reaction is the oxidative cleavage of the Se-Se bond in diphenyl diselenide 2a by Oxone ® , forming intermediates A and B (Perin et al, 2018). Once the electrophilic selenium species A is formed, it…”
Section: Insert Figure 3 Heresupporting
confidence: 60%
“…Based on our results and those from the literature (Zhang, Sarkar & Larock, 2006;Recchi, Back & Zeni, 2017;Perin et al, 2018), a plausible mechanism for the carbocyclization of alkynol 1a with (C 6 H 5 Se) 2 2a/Oxone ® in aqueous medium is depicted in Scheme 2. The first step in the reaction is the oxidative cleavage of the Se-Se bond in diphenyl diselenide 2a by Oxone ® , forming intermediates A and B (Perin et al, 2018). Once the electrophilic selenium species A is formed, it…”
Section: Insert Figure 3 Heresupporting
confidence: 60%
“…Oxone ® (2KHSO 5 ⋅KHSO 4 ⋅K 2 SO 4 ) acts as oxidant in many selective oxidation reactions [16] and it has been used to synthesize several heterocyclic compounds by intra- [17][18][19][20][21][22][23][24] and intermolecu-lar reactions, [25][26][27][28][29] including oxidative cyclization ones. [30][31][32][33][34][35][36] Recently, our group has explored the application of this oxidant in the synthesis of organoselenium and organotellurium compounds, [37][38][39][40][41][42] such as 2,3-bis-organochalcogenyl-benzo [b] chalcogenophenes, via the electrophilic cyclization of 2functionalized selanyl-and sulfanylalkynes (Scheme 1a). [43] In parallel, cyclization of enynes represents a versatile strategy for accessing cyclic compounds, specially due to the high atom-economy and excellent functional group tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…49 Our research group recently reported the use of Oxone ® to generate electrophilic species of selenium evidencing its application in selenylation reactions. [50][51][52][53][54] As an example, we reported an alternative metal-free methodology for the synthesis of diorganyl selenides and tellurides mediated by Oxone ® . 51 Other examples include the selenomethoxylation of inactivated alkenes, 52 the synthesis of 2-organoselanylnaphthalenes under ultrasonic irradiation, 53 the selective synthesis of 5-arylselanyl-imidazo[2,1-b]thiazoles, 3-arylselanyl-imidazo[1,2-a]pyridines and 4-arylselanyl-1H-pyrazoles derivatives via direct selenylation C-Se coupling reaction mediated by Oxone ® .…”
Section: Introductionmentioning
confidence: 99%